Analisis Manajemen Risiko pada UMKM DND Fashion - Mario Maulana Wardhana; Muhammad Alfin Alfarizi; Muhammad Shoffan Anbiya; Nisa Febrianti; Almaira Sarah Junjunan5 (Indo Publishing, 2026)
This study aims to analyze the risk management practices implemented by DND Fashion, a Micro, Small, and Medium Enterprise (MSME) that specializes in custom clothing production. With the increasing competition and rapid shifts in fashion trends, MSMEs need to identify and mitigate risks to ensure sustainable business operations. This research uses a qualitative descriptive approach supported by SWOT analysis and risk identification derived from operational data. The findings reveal that DND Fashion faces market risks, operational risks, and human resource risks. Recommended strategies include product innovation, digital marketing optimization, equipment maintenance, and skill enhancement for workers. This study provides practical recommendations to strengthen risk management in MSME fashion businesses.